Robotic Ureteral Reconstruction in the Pediatric Population - Bilgutay, Aylin N.; Kirsch, Andrew J. (Frontiers in Pediatrics, 2019)
Robot-assisted laparoscopic (RAL) surgery is a safe, minimally invasive technique that has become more widely used in pediatric urology over recent decades. With several advantages over standard laparoscopy, robotic surgery is particularly well-suited to reconstructive surgery involving delicate structures like the ureter. A robotic approach provides excellent access to and visualization of the ureter at all levels. Common applications include upper ureteral reconstruction (e.g., pyeloplasty, ureteropelvic junction polypectomy, ureterocalicostomy, and high uretero-ureterostomy in duplex systems), mid-ureteral reconstruction (e.g., mid uretero-ureterostomy for stricture or polyp), and lower ureteral reconstruction (e.g., ureteral reimplantation and lower ureter-ureterostomy in duplex systems). Herein, we describe each of these robotic procedures in detail.